Verschillende ongelijkheden? The new history of old inequality en Oorlog en ongelijkheid - Hilkens, Bram (TSEG - The Low Countries Journal of Social and Economic History, 2025)
Studies on economic inequality in the past have rapidly risen to prominence in recent years. Oorlog en ongelijkheid reminds us that inequality manifests not only in aggregate disparities in income or wealth, but also in uneven access to political decision-making, affecting everyday experiences. Both the history of inequality and scholars working with the concept of inequality historically can deepen our understanding of economic disparities by more integrally approaching inequality as an abstract structure with real life material consequences.